Treatment for the Transmission of Coronavirus Disease 2019 from Human to Human by Hand as Divine Creators Code 19 - Hossain, Mohammad Abul (British Journal of Healthcare and Medical Research, 2020)
On 11 February 2020, the WHO declared the Coronavirus disease 2019 (COVID-19) as a new pandemic defined as the illness caused by a novel coronavirus now called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which was first identified amid an outbreak of respiratory illness cases in Wuhan City, Hubei Province, China. It has not been previously identified in humans but WHO mentioned the virus, SARS-CoV-2 is transmitted from human to human by hand. The COVID-19 has been spreading rapidly across the world, affecting more than 185 countries. Up to 11 May 2020, over four million people are infected and over one fourth of million individuals around the world have died from the COVID-19. Till now, there is no approved medicine to prevent COVID-19 infection. WHO said, it is one year away to receive COVID-19 vaccine. The above panic situation and global pandemic insists me to consider, it is the Third World War of Divine Creator, Allah by Bio-weapon due to Human’s recent activity against the Creator such as modification of the Holy Qur’an, insulting the Prophet Muhammad (peace be upon him), etc. This paper presents the evidence of the involvement of Divine Creator in this pandemic, and the transmission of COVID-19 by human hand is simulated with the Divine Creator’s Code “19”. Based on the simulation, a probable treatment process is proposed to immediate relief of mankind from COVID-19. Again, evaluated by Divine Creator’s Code 19, it is suggested that the vaccine mRNA-1273, developed at the biotechnology company Moderna in Massachusetts, could be applicable (2-dose schedule at Day 57) to prevent infection with SARS-CoV-2 causes the disease COVID-19 but it is taking time for testing of safe and effectiveness which is going on in the National Institute of Allergy and Infectious Diseases Research Center in the United States of America.